Exploring the Challenges and Strategies in Learning English as a Foreign Language: A Qualitative Study at IAINU Bangil - Munawaroh, Siti; Uswatun Hasanah, Nadiyatul (Institut Agama Islam Negeri Palopo, 2025)
Learning English as a foreign language presents unique challenges for students, particularly in educational settings where resources and exposure to the language are limited. This qualitative study explores the difficulties faced by students at IAINU Bangil, a higher education institution in Indonesia, in acquiring English proficiency, as well as the strategies employed to overcome these barriers. Data were collected through semi-structured interviews, classroom observations, and focus group discussions with students and instructors. The findings reveal three primary challenges: (1) limited speaking proficiency due to insufficient practice opportunities, (2) reluctance to engage in English communication despite adequate vocabulary knowledge, and (3) inadequate institutional support, including the absence of language laboratories and standardized libraries. Conversely, effective strategies identified include creating supportive learning environments, encouraging consistent vocabulary acquisition, and integrating English into daily routines. The study highlights the critical role of institutional support and innovative teaching approaches in fostering English language acquisition. These insights contribute to a deeper understanding of foreign language learning dynamics and offer practical recommendations for educators and policymakers in similar contexts.